Patient-centredness and consumerism in healthcare: an ideological mess. - Latimer, T; Roscamp, J; Papanikitas, A (SAGE Publications, 2017)
In this paper we contrast two concepts that permeate political rhetoric concerning healthcare in the UK and elsewhere: patient centred care and consumerism. We outline their parallel histories and note that they appear to have different philosophical origins. Both concepts, however, are founded in the value or rights of the patient, whether as a person or as a buyer of services. As these concepts are variously defined or even misinterpreted, we note that this creates opportunities for their rhetorical use in ways that appear insincere. We outline the main problems with conflating patient centred care and consumerism, arguing that these rest on conceptually messy argument and incorrect or insincere definitions of consumerism. We further argue that consumerism is not compatible with a rationed healthcare service but patient-centred care arguably is.